The Gluteus Medius Vs. Thigh Muscles Strength Ratio and Their Relation to Electromyography Amplitude During a Farmer's Walk Exercise - Stastny, Petr; Lehnert, Michal; Zaatar, Amr; Svoboda, Zdenek; Xaverova, Zuzana; Pietraszewski, Przemysław (Journal of human kinetics, 2015)
The strength ratio between hamstrings and quadriceps (H/Q) is associated with knee injuries as well as hip abductor muscle (HAB) weakness. Sixteen resistance trained men (age, 32.5 ± 4.2 years) performed 5 s maximal isometric contractions at 75° of knee flexion/extension and 15° of hip abduction on a dynamometer. After this isometric test they performed a Farmer's walk exercise to find out if the muscle strength ratio predicted the electromyography amplitude expressed as a percentage of maximum voluntary isometric contraction (%MVIC). The carried load represented a moderate intensity of 75% of the exercise six repetitions maximum (6RM). Electromyography data from the vastus medialis (VM), vastus lateralis (VL), biceps femoris (BF) and gluteus medius (Gmed) on each leg were collected during the procedure. The groups selected were participants with H/Q ≥ 0.5, HQ < 0.5, HAB/H ≥ 1, HAB/H < 1, HAB/Q ≥ 0.5 and HAB/Q < 0.5. One way ANOVA showed that Gmed activity was significantly greater in the group with HAB/H < 1 (42 ± 14 %MVIC) as compared to HAB/H ≥ 1 (26 ± 10 %MVIC) and HAB/Q < 0.5 (47 ± 19 %MVIC) compared to HAB/Q ≥ 0.5 (26 ± 12 %MVIC). The individuals with HAB/H < 1 were found to have greater activation of their Gmed during the Farmer's walk exercise. Individuals with HAB/Q < 0.5 had greater activation of the Gmed. Gmed strength ratios predict the muscle involvement when a moderate amount of the external load is used. The Farmer's walk is recommended as an exercise which can strengthen the gluteus medius, especially for individuals with a HAB/H ratio < 1 and HAB/Q < 0.5.
Keywords: isometric strength; loaded walking; hip abduction; MVIC; electromyography